Characterization of low-nitrogen quantum diamond for pulsed magnetometry applications - Tang, Jiashen; Roncaioli, Connor A.; Edmonds, Andrew M.; Davidsson, Atli; Hart, Connor A.; Markham, Matthew L.; Walsworth, Ronald L. (Frontiers in Quantum Science and Technology, 2025)
Ensembles of nitrogen-vacancy (NV) centers in diamond are versatile quantum sensors with broad applications in the physical and life sciences. The concentration of neutral substitutional nitrogen ([Ns0]) strongly influences NV electronic spin coherence times, sensitivity, and optimal sensing strategies. Diamonds with [Ns0] ∼ 1–10 ppm are a focus of recent material engineering efforts, with higher concentrations being favorable for continuous-wave optically detected magnetic resonance (CW-ODMR) and lower concentrations expected to benefit pulsed magnetometry techniques through extended NV spin coherence times and improved sensing duty cycles. In this work, we synthesize and characterize low-[Ns0] (∼0.8 ppm), NV-enriched diamond material, engineered through low-strain chemical vapor deposition (CVD) growth on high-quality substrates, 12C isotopic purification, and controlled electron irradiation and annealing. Our results demonstrate good strain homogeneity in diamonds grown on CVD substrates and spin-bath-limited NV dephasing times. By measuring NV spin and charge properties across a wide range of optical NV excitation intensity, we provide direct comparisons of photon-shot-noise-limited magnetic field sensitivity between the current low-[Ns0] and previously studied higher-[Ns0] (∼14 ppm) NV-diamond sensors. We show that low-[Ns0] diamond can outperform higher-[Ns0] diamond at moderate and low optical NV excitation intensity. Our results provide practical benchmarks and guidance for selecting NV-diamond sensors tailored to specific experimental constraints and sensing requirements.